The opinion of patients with mental disorder about tobacco and its prohibition in psychiatric hospitalization - Renata Marques de Oliveira; Antonia Regina Ferreira Furegato (Revista da Escola de Enfermagem da USP, 2014)
Objective: To identify the opinion of patients with mental disorder about tobacco and its prohibition during psychiatric hospitalization. Method: An exploratory study with 96 patients smokers with mental disorders hospitalized in a psychiatric ward of a general hospital. The interviews were conducted individually, using an instrument designed for this study. The content from the interviews was recorded, transcribed and submitted to a thematic content analysis. Results: The patients with mental disorder were identified as perceiving smoking during the psychiatric hospitalization as a help to support the difficulties in socialization and in the lack of activities. The permission for smoking is seen as a signal of respect to their needs. The subjects mentioned to not accept the total smoking prohibition. Conclusion: Tobacco helps to face difficulties and conflicts in the psychiatric hospitalization. There is resistance regarding the possibility to totally withdraw the smoking permission during hospitalization.